PERBANDINGAN METODE GARISMATIKA DENGAN METODE PERKALIAN BERSUSUN UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN PESERTA DIDIK KELAS IV SDN SERANG 9 - Bintang, Raynanda; Yandari, Indhira Asih Vivi; Alamsyah, Trian Pamungkas (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to compare the use of the Garismatika method with the traditional column multiplication method in improving multiplication calculation skills among fourth-grade students at Sekolah Dasar Negeri Serang 09. The research method is quantitative with a nonequivalent control group design. The study sampled fourth-grade students, with each class consisting of 26 students. The results show that students who used Garismatika method demonstrated better improvement in multiplication skills compared to those who used the column multiplication method. The improvement in multiplication calculation skills is supported by hypothesis data obtained from the post-test results between the experimental and control groups, with a t-test value of 2.10 and a t-table value of 2.06. Additionally, the N-Gain data in the experimental group was 0.56, compared to 0.41 in the control group.